Implementasi Strategi Pemasaran Digital Melalui E-Commerce Shopee pada UMKM Keripik Putri Sari Desa Wonokerto - Moch Rizky Khairul Rachman; Yanda Bara Kusuma (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
It cannot be denied that the digital era has developed greatly in today's society, especially among teenagers. All groups from children to the elderly are technologically literate because the world has begun to evolve. This allows people to enjoy and maintain their motivation in following existing technological developments, including the fields of social media and e-commerce which cannot be separated from the Internet. Media advertising using Internet technology or other technological media is commonly referred to as e-commerce, which has the advantage of being able to carry out buying and selling activities between sellers, and applications using Internet technology to make online purchases. Usually, the e-commerce widely used by business players is Shopee.The appearance of the website is attractive and easy to understand, which is an important thing for the public to pay attention to in e-commerce. Nowadays, small and medium-sized business stakeholders are beginning to realize that society is showing more interest in online shopping, as consumers are also embracing the development of digital pursuit technology and no longer need to go to a shopping place to get the goods they want, what is offered in e-commerce is no less competitive